A flipped learning experience in geography: a qualitative study using focus group discussion - Mohd Isa, Nor Kalsum; Che Leh, Fauziah; Mohd Isa, Nor Junainah; Mohd Yunos, Mohd Yazid; Othman, Shahrina; Ibrahim, Mohd Hairy (Semarak Ilmu Publishing, 2023)
Flipped learning (FL) is gaining broader acceptance in geography education. This study aims to explore the remaining question concerning how the FL approach is associated with students' understanding of Geography course content. A focus group discussion (FGD) was conducted in a protocol through nine groups of students consisting of six to ten members per group. In total, eighty-eight undergraduate geography students had taken part in the discussion. Qualitative data obtained from the FGD were coded and thematically analyzed. The qualitative analysis revealed four major themes: (i) attention to learning geography, (ii) personal needs in learning geography (iii) confidence to succeed in learning geography, and (iv) satisfaction in learning geography associated with students' understanding of the course content. The results reveal that the understanding of the students of the course content was high through the application of the FL approach to teaching and learning. The finding is very significant to provide a guideline for FL application at the university level, specifically for Geography Module to increase students understanding of the course content.